EKSLUSI DAN INKLUSI PADA MEDIA VIVA.CO.ID EDISI DESEMBER 2022 (ANALISIS WACANA KRITIS MODEL THEO VAN LEEUWEN) - Iceu Hidayanti; Agus Hamdani (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2023)
Technological advancements have led humanity towards practicality in various aspects. The same applies to the realm of information, which moves faster and more agilely in its changes. Therefore, mass media plays a role and has control in shaping public opinion regarding certain events. The use of critical theory as a tool for examination and analysis in this research aims to observe the representation of news on Viva.co.id regarding the controversial Rabbani Advertisement Video case. This study primarily focuses on highlighting Rabbani as the marginalized party in the news coverage. The research adopts a qualitative approach using content analysis as the method. The study is limited to one news text published in a single section of Viva.co.id. The discourse analysis model employed is Theo Van Leeuwen's model, with the aim of examining and detecting how Rabbani is marginalized in a discourse. The research findings reveal the presence of one type of exclusion, namely nominalization, while inclusion comprises three types: differentiation, abstraction, and identification. The limitations of this study are due to the fact that it solely focuses on one news text. Keywords: Exclusion and inclusion, critical discourse, Theo Van Leeuwen.